MORPHOFUNCTIONAL CHARACTERISTICS OF FIBROBLASTS (MCCOY CELL LINE) CULTURED WITH MAGNESIUM PREPARATIONS - L. V. Didenko; T. G. Borovaya; E. A. Kost; E. A. Ulubieva; A. V. Timofeeva; A. G. Avtandilov (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of magnesium orotate, magnesium/pyridoxine combination and magnesium sulfate on fibroblast morphofunctional characteristics in cell culture of fibroblasts (McCoy line).Material and methods. The study of fibroblasts (McCoy line) with the addition of magnesium-containing preparations (magnesium orotate, magnesium/pyridoxine combination, magnesium sulphate) to the culture medium was performed using scanning and transmission electron microscopy.Results. When adding into the media magnesium orotate or magnesium/pyridoxine combination, significant changes in morphofunctional state of fibroblasts were noted, which were absent when adding magnesium sulfate. At that fibroblasts significantly promoted synthetic and secretory activity. This was expressed in the formation of amorphous and fibrous components in well-formed cell layers.Conclusion. Stimulation by magnesium ions of the proliferative activity of fibroblasts is shown in the morphological analysis of the effect of magnesium orotate or magnesium in combination with pyridoxine and magnesium sulfate on morphological and functional organization of fibroblasts. Revealed the predominant influence of magnesium orotate, and a less pronounced effect of magnesium in combination with pyridoxine on biosynthetic processes in the cells, including the synthesis of amorphous and fibrous components (protocollagen and elastin) of the extracellular matrix founded.